The association between histological chorioamnionitis, funisitis and neonatal outcome in women with preterm prelabor rupture of membranes. (16th April 2013) - Tsiartas, Panagiotis; Kacerovsky, Marian; Musilova, Ivana; Hornychova, Helena; Cobo, Teresa; Sävman, Karin; Jacobsson, Bo
Abstract: Objective : To determine the impact of histological chorioamnionitis (HCA) and funisitis on neonatal outcome in preterm prelabor rupture of membranes (PPROM) pregnancies. Methods : Women with PPROM between 24 + 0 to 36 + 6 weeks of gestation, admitted to the Department of Obstetrics and Gynecology at the University Hospital Hradec Kralove in the Czech Republic, between July 2008 and October 2010, were enrolled in the study ( n  = 231). Results : The incidence of early-onset sepsis (EOS) differed significantly in neonates born to women with and without HCA, after adjustment for gestational age (11% versus 1%, p  = 0.011). The incidence of EOS in neonates was also significantly different, after adjustment for gestational age, in cases with and without funisitis (18% versus 4%, p  = 0.002). The same was also found for retinopathy of prematurity (ROP) cases with and without funisitis (23% versus 4%, p  = 0.014), after adjustment for gestational age. Conclusions : HCA and funisitis increase the risk of adverse perinatal outcome in PPROM pregnancies.